Push, pull, and push-back to land certification: Regional dynamics in pilot certification projects in Côte d'Ivoire - Catherine Boone (London School of Economics and Political Science (LSE), Department of International Development, 2020)
Since 2000, many African countries have moved toward land tenure reforms that aim at comprehensive land registration (or certification) and titling. Much work in political science and in the advocacy literature identifies recipients of land certificates or titles as "program beneficiaries," and political scientists have modeled titling programs as a form of distributive politics. In practice, however, land registration programs are often divisive and difficult to implement. This paper tackles the apparent puzzle of friction around land certification. We study Côte d'Ivoire's rocky history of land certification from 2004 to 2017 to identify political economy variables that may give rise to heterogenous and even conflicting preferences around certification. We identify regional inequalities, social inequalities, and regional variation in pre-existing land tenure institutions as factors that help account for friction or even resistance around land titling, and thus the difficult politics that may arise around land tenure reform. Land certification is not a public good or a private good for everyone.
Keywords: 330; land; Côte d'Ivoire; inequalities; political economy; land tenure